2009
DOI: 10.1080/09637480701752210
|View full text |Cite
|
Sign up to set email alerts
|

Serum vitamin A in mothers and newborns in the city of Rio de Janeiro

Abstract: Retinol and carotenoid levels were determined spectrophotometrically in the blood of 222 mothers at delivery and in the umbilical cord of the newborns. We observed an important prevalence of vitamin A deficiency (VAD) among mothers and newborns (25.4% and 46.2%, respectively) as well as carotenoid inadequacy (52.3% and 92.6% in mothers and newborns, respectively), and an increased risk of VAD development among newborns whose mothers had VAD (odds ratio = 4.79). We found an increased risk of carotenoid inadequa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…No studies assessing specific micronutrient maternal levels were included in this review because of IPI categorisations that did not meet inclusion criteria. Although some evidence indicates that decreases in some micronutrients may be more prevalent in women with short IPIs, 54–57 differences in vitamins and IPIs assessed and possible residual confounding are factors that need to be explored as research in this area expands.…”
Section: Resultsmentioning
confidence: 99%
“…No studies assessing specific micronutrient maternal levels were included in this review because of IPI categorisations that did not meet inclusion criteria. Although some evidence indicates that decreases in some micronutrients may be more prevalent in women with short IPIs, 54–57 differences in vitamins and IPIs assessed and possible residual confounding are factors that need to be explored as research in this area expands.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple linear regression analyses with adjustment for maternal age, VA intake, and BMI did not show an association between retinol concentrations in maternal blood and UC blood (estimate ¼ 0.09; 95% CI ¼ À0.007-0.2; R 2 ¼ 0.08; p ¼ 0.07), or between those in maternal blood and BM (estimate ¼ À0.76; 95% CI ¼ À2.43-0.91; R 2 ¼ 0.07; p ¼ 0. 36). No association was observed between maternal VA intake and retinol concentrations in maternal blood, BM, or UC blood when the data were analysed by multiple linear regression with adjustment for maternal age and BMI.…”
Section: Variablesmentioning
confidence: 89%
“…Low retinol concentrations in newborns may be attributed to regulation of VA transfer through the placenta because high concentrations may have adverse effects on the foetus. 36,38,39 Additionally, the high prevalence of mothers with insufficient serum retinol concentrations could contribute to an explanation of this finding. This is because neonates of mothers with deficient retinol concentrations showed significantly lower retinol concentrations in UC blood compared with those born to mothers without inadequate serum retinol concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, as living standards have improved, the VAD rates of adults and older children have fallen significantly worldwide (12). However, the percentage of neonates with VAD remains as high as 42-82% according to some studies (13)(14)(15)(16). In a previous study, we also found a high incidence of neonatal VAD (60.1%) in areas where VAD was uncommon (17,18).…”
Section: Introductionmentioning
confidence: 58%